2022
DOI: 10.32598/jsmj.20.6.1889
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educational Intervention Based on Health Belief Model on Blood Pressure Control in Patients With Hypertension Referring to the Clinic of Shariati Hospital in Isfahan 2017-2018

Abstract: Introduction: Hypertension is the most important risk factor for death and cardiovascular disease (CVD). Blood was referred to the clinic of Shariati Hospital in Isfahan in 2017-2018. Methods: The present study was a clinical trial with a pretest- post test design with a control group. 90 patients with hypertension referred to the internal clinic of Shariati Hospital were randomly divided into two groups of 45 people (control and intervention). For the intervention group, training based on health belief model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The present findings showed that although there was no significant difference between the two groups in terms of perceived barriers before the educational intervention, the educational intervention reduced the barriers faced by patients in performing self-care behaviors in the intervention group. This finding was consistent with the results of studies conducted by Mohsenipouya et al [18], Sharp et al [21], Bakhshi et al [22], Shojaeifar et al [23], and Lari et al [20]. The results of a study by Sharp et al; [21] designed to determine the effectiveness of an educational intervention on self-efficacy and perceived barriers to healthy eating in cardiovascular patients over a period of 6 to 12 weeks after discharge showed that perceived barriers to healthy eating intake decreased significantly after the intervention.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings showed that although there was no significant difference between the two groups in terms of perceived barriers before the educational intervention, the educational intervention reduced the barriers faced by patients in performing self-care behaviors in the intervention group. This finding was consistent with the results of studies conducted by Mohsenipouya et al [18], Sharp et al [21], Bakhshi et al [22], Shojaeifar et al [23], and Lari et al [20]. The results of a study by Sharp et al; [21] designed to determine the effectiveness of an educational intervention on self-efficacy and perceived barriers to healthy eating in cardiovascular patients over a period of 6 to 12 weeks after discharge showed that perceived barriers to healthy eating intake decreased significantly after the intervention.…”
Section: Discussionsupporting
confidence: 93%
“…The results of a study by Sharp et al; [ 21 ] designed to determine the effectiveness of an educational intervention on self-efficacy and perceived barriers to healthy eating in cardiovascular patients over a period of 6 to 12 weeks after discharge showed that perceived barriers to healthy eating intake decreased significantly after the intervention. Shojaeifar et al [ 23 ] in a study conducted among patients with hypertension found that there was a statistically significant difference between the mean of the main indicators of sensitivity, severity, benefits and barriers in the intervention and control groups before and after the intervention. These researchers managed to promote self-care behaviors in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%